Perbandingan Metode Dematel Dan Edas Pada Pemilihan Karyawan Kerok Terbaik - Zai, Winda Ningsi (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
Swallow is one of the local products that are in great demand by entrepreneurs in the city of Medan for cultivation of PT. Efyanto walet as a limited company engaged in the trade and services of Swallow distributors has a very important role in meeting the needs of consumer demand for the availability of swallow nests. Common problems that often occur when selecting the best employees are often there is a lack of transparency, undocumented exposure to the criteria value used by both selectors, and there is still a lot of discrimination found. With the decision support system to get the best alterntif results from problems that often occur. Therefore, the method used is the Dematel and Edas methods thus carried out the establishment of both methods for the right solution to solve the problem.